Avian myeloblastosis virus proteins in leukemic chicken myeloblasts. - Silva, R F (1980)
We have analyzed the avian myeloblastosis virus proteins in two types of leukemic myeloblasts: established myeloblastic cell lines (DU 1765 and DU 11157) and leukemic myeloblasts obtained from the peripheral blood of a leukemic C/E Spafas chicken (no. 21957). Using monospecific antisera for immunoprecipitation and polyacrylamide gel electrophoresis, we have detected gag gene-related proteins in the myeloblasts. The DU 1765 and DU 11157 cells contained a p100 protein which possessed antigenic determinants of the viral proteins p27, p19, p15, and p12. The p100 was not found in leukemic myeloblasts from Spafas chickens, and pulse-chase experiments showed that the p100 was not a precursor for the viral proteins. However, the p100 is present in uninfected line 15 chicken embryos. A pr76-like protein was identified in DU 1765 cells but migrated slightly further into gels than the pr76 of Spafas-derived leukemic myeloblasts. The Spafas-derived myeloblasts produced a pr60, whereas the DU 1765 cells contained instead a related protein of 62,000 daltons. Using anti-avian myeloblastosis virus gp85 sera, a glycoprotein of 120,000 daltons (gp120) was detected in all the tested leukemic myeloblasts. The gp120 was also present, in low amounts, in uninfected embyonic spleen and yolk sac cells. The anti-gp85 sera also precipitated a 27,000-dalton protein (h27) in these same cells. Both the gp120 and h27 could not be detected in either uninfected or myeloblastosis-associated virus-infected fibroblasts. Limited peptide hydrolysis revealed that h27 is different from the viral structural protein p27. In conclusion, monospecific antisera for gag and env gene products of avian myeloblastosis virus did not precipitate any unique or aberrant avian myeloblastosis virus protein from leukemic myeloblasts.